2011
DOI: 10.1007/s10904-011-9569-4
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticles Supported on Poly(2-hydroxyethyl methacrylate)/KIT-6 Composite as an Efficient and Reusable Catalyst for Suzuki–Miyaura Reaction in Water

Abstract: Pd nanoparticle-poly(2-hydroxyethyl methacrylate)/KIT-6 (Pd-PHEMA/KIT-6) composite was fabricated through in situ polymerization method and was evaluated as a novel heterogeneous catalyst in SuzukiMiyaura cross coupling reactions of aryl halides and phenylboronic acid in an aqueous medium. The catalyst was characterized by XRD, FT-IR, UV-Vis, TG, BET, and TEM techniques. The results revealed that the supported catalyst Pd-PHEMA/KIT-6 exhibited excellent catalytic activity for the coupling of aryl iodides, aryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The bands at 1080, 817, and 470 cm −1 are related to Si-O-Si asymmetrical stretching vibration, symmetrical stretching vibration and bending vibration, respectively, which are related to KIT-6 and KIT-6/Poly(AA-EGDMA) [23]. In addition, the FTIR of KIT-6 shows the band around 945-957 cm −1 , which is assigned to Si-OH vibrations of silanols in the surface that refer to the characteristics of mesoporous silica [23]. The FTIR spectrum of KIT-6 contains the broad band around 3448 cm −1 which is assigned to the O-H stretching of water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands at 1080, 817, and 470 cm −1 are related to Si-O-Si asymmetrical stretching vibration, symmetrical stretching vibration and bending vibration, respectively, which are related to KIT-6 and KIT-6/Poly(AA-EGDMA) [23]. In addition, the FTIR of KIT-6 shows the band around 945-957 cm −1 , which is assigned to Si-OH vibrations of silanols in the surface that refer to the characteristics of mesoporous silica [23]. The FTIR spectrum of KIT-6 contains the broad band around 3448 cm −1 which is assigned to the O-H stretching of water.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the hydroxyl stretching of hydrogen bonded internal silanol groups appears in this range. The peak at 1635 cm −1 corresponds to the bending mode of OH of water [23]. The FTIR spectrum of AA-copolymer (poly-(AA-EGDMA)) contains the peak at 1726 cm −1 that is related to the (C=O) bond stretching vibration of the carbonyl group of AA [22].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have suggested that under C C bond forming reaction conditions the employed palladium(II) pre-catalysts (soluble or supported ones) generate palladium nanoparticles [43,62,63], which can leach in solution if immobilized onto an insoluble matrix. These nanoparticles may in turn generate soluble palladium(0) mononuclear (or dinuclear) complexes in equilibrium with them [62,64].…”
Section: Pd-polmentioning
confidence: 99%
“…In fact, despite of the large number of reports concerning the use of polymer supported catalysts for promoting the Suzuki reaction in water, there are still margins of improvement. First of all the supported catalysts are generally less active (Pd mol% ≥ 0.1) than their homogeneous counterparts [12,14,16,43] (with homogeneous catalysts sometimes homeopathic concentration of palladium are sufficient [9,44]). In some cases supported catalysts suffer of considerable metal leaching and very often they are not able to promote the coupling of the aryl chlorides (more evaluable from an industrial point of view) [12,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…97 Other examples include the use of polymerinorganic hybrid materials as support for Pd-NP catalysts for coupling reactions. 98 Pd-NPs supported in tetraalkylammonium salts were shown to activate aryl chlorides. Using these Pd-NPs in a mixture of water, long-chain alkylammonium salts, and NBu 4 OH as base, biaryl products with excellent yields in short times (3-5 h) were obtained.…”
Section: Palladium Nanocatalystsmentioning
confidence: 99%